SOLAR PHOTOVOLTAIC (PV) WITH STATCOM FEATURE TO IMPROVE POWER QUALITY FOR DISTRIBUTION WITH MATLAB TOOL - Dr. P. Karpagavalli, Chougale Rajkumar Kundlik (International Journal of Advanced Science and Technology, 2020)
This paper demonstrates grid associated solar photovoltaic (PV) system with reactive power control as a STATCOM called as PV Solar STATCOM. A MATLAB tool gives a specific idea about the real and reactive power flow to the power system. A voltage source inverter (VSI) actually provides both real as well as reactive power to the grid as per the load demands. A reactive power flow in an power system defines the Power Quality (PQ), therefore needs to compensate. This is possible by means of PV solar STATCOM which enhances the quality of power and minimizes harmonics. A non-linear load is the principle cause of harmonics, while the PV system establishes power converters which are enormously producing source of harmonics. In this paper, the harmonics are controlled by a photovoltaic system (PV) on a distribution side by utilizing STATCOM feature with the use of MATLAB tool, which further improves power factor and therefore power quality as well.